Mood states of non-professional soccer referees Estados de humor de árbitros de futebol não-profissional - Ribeiro H.N.* (2012)
This study evaluated the mood state of non-professional soccer referees in pre-competitive period. To this end, 25 referees from the southern Brazil have participated. Data were collected before participation in matches of a local competition, using the characterization questionnaire and Brunel Mood Scale-BRUMS. Were used comparison (Mann-Whitney; Kruskal-Wallis) and correlation tests (Spearman) (p< 0.05). Referees who do not get sick had less fatigue and tension. Lower depression was observed in those with better quality of sleep. Assistant referees had higher tension and fatigue than the principal referees. Those who participated in professional matches had higher vigor. The age was negatively correlated with anger, confusion and tension. Tension was negatively correlated with the time of experience in arbitration. Concluding, the mood state of non-professional soccer referees in pre-competitive situation is related to the self-evaluation of health, sleep, function and experience in arbitration and age.